THE ROLE OF OXIDATIVE STRESS IN OVARIAN CANCER PATHOGENESIS - Simić, Petar; Plješa Ercegovac, Marija; Ćorić, Vesna; Pažin, Vladimir (Srpski medicinski časopis Lekarske komore, 2024)
Ovarian cancer is the deadliest form of gynecological malignancy. The presence of non-specific symptoms, together with the identification of the disease in an advanced stage, are the primary determinants of an unfavorable prognosis, resulting in an overall five-year survival rate of 45%. Currently, the treatment of choice for ovarian cancer is surgery aimed at completely removing the illness macroscopically, along with adjuvant chemotherapy. The significance of early diagnosis is evident in the several conducted prospective studies, which have not identified a successful method for early identification of this disease. Oxidative stress (OS) is a well-established contributor to carcinogenesis in several types of malignancies. It occurs when there is an imbalance between the production and clearance of reactive oxygen species. These molecules affect both pathological and physiological processes. Literature findings indicate that oxidative stress has a role in the development and pathophysiology of ovarian cancer by affecting the following four areas of cellular functioning: (i) genetic alterations, (ii) signaling pathways, (iii) transcription factors, and (iv) tumor microenvironment. Reactive oxygen species can induce mutations, which initiate the formation, proliferation, and maturation of tumor tissue. Also, prolonged elevation of the concentration of free radicals harmfully affects cells, causing the initiation of apoptotic pathways. Specifically, the presence of free radicals leads to the impairment of biomolecules and the creation of byproducts from this interaction. Consequently, these compounds may be found in various body structures and products such as tissue, plasma, urine, and other, where they can be detected. The study aims to enhance the readers' understanding of the pathogenesis of ovarian cancer, which is characterized by its undetermined cause and diverse nature. Previous research has primarily focused on surgical or medicamentous treatment, therefore the present study aims to shed light on the role of oxidative stress in this process.
Keywords: ovarian cancer; oxidative stress; pathogenesis of ovarian cancer